Feminism Values in the Posters of Yogyakarta’s Students Demonstration: The #Gejayanmemanggil - Nurul Huda Gustema; Dr. Wening Sahayu (Bina Nusantara University, 2020)
The research aimed to examine feminism values on the posters of Yogyakarta’s students’ demonstration the #Gejayanmemanggil. Data collection technique was conducted by reading and note-taking techniques. From social media (Instagram), read the posters for several times, made a reduction for the data, and analyzed the feminism values which were reflected in the data based on the discourse or textual aspects. In the findings, the use of feminist languages, which contained the feminism values was revealed, in order to correlate it with the previous studies and theories. It was affected by the positive and negative meanings of the words and their impact on the audience. Discourse analysis was the proper way to examine the hidden ideologies of discourse. It revealed the discursive structures and manipulative language of the speakers or writers. The results reveal that the posters on the demonstration #Gejayanmemanggil contain feminism values as reflected in the feminist languages which support the ideology. Therefore, based on the findings of the research which conducts a discourse analysis in examining mass communication, language has enormous powers in appealing to emotions, manipulating someone’s thoughts and behavior, as well as misrepresenting the realities.